Algebraic and Geometric Methods in Statistics 2009
DOI: 10.1017/cbo9780511642401.006
|View full text |Cite
|
Sign up to set email alerts
|

Markov chains, quotient ideals and connectivity with positive margins

Abstract: We present algebraic methods for studying connectivity of Markov moves with margin positivity. The purpose is to develop Markov sampling methods for exact conditional inference in statistical models where a Markov basis is hard to compute. In some cases positive margins are shown to allow a set of Markov connecting moves that are much simpler than the full Markov basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Rapallo and Yoshida48 study Markov subbases for bounded contingency tables for the model of independence. It has been shown that in some cases, a smaller set of moves suffices under the condition of positive margins, for example, Chen et al49 and Hara et al50 demonstrate this in case of exact logistic regression. More recently, Kahle et al51 have studied the positive margin property and its generalization called the interior point property for graphical models by studying primary decompositions of conditional independence ideals.…”
Section: Computing Markov Basesmentioning
confidence: 98%
See 1 more Smart Citation
“…Rapallo and Yoshida48 study Markov subbases for bounded contingency tables for the model of independence. It has been shown that in some cases, a smaller set of moves suffices under the condition of positive margins, for example, Chen et al49 and Hara et al50 demonstrate this in case of exact logistic regression. More recently, Kahle et al51 have studied the positive margin property and its generalization called the interior point property for graphical models by studying primary decompositions of conditional independence ideals.…”
Section: Computing Markov Basesmentioning
confidence: 98%
“…A related basis called lattice basis works by allowing the Markov chain to have tables with values such as −1, for example, see Refs 49, 52, and also Ref 53 for advantages and disadvantages of lattice bases in comparison to Markov bases. This idea of going outside the original fiber that has only nonnegative tables, has been used in cases where Markov bases are difficult to compute for the original fiber ℱ 0 but easier for an enlarged fiber ℱ 1 by using the Lawrence lifting.…”
Section: Computing Markov Basesmentioning
confidence: 99%
“…[11], [2], [3]), this result is closely related to connectivity of a specific fiber by a subset of a Markov basis. See [4], [1], [12] for relevant results. Since a Markov basis for the whole configuration of elementary imsets is very complicated ( [5]), it is remarkable that F A,B | C is connected by the two-by-two basic relations.…”
Section: Theorem 1 Every F Ab | C Is Connected By Two-by-two Basic mentioning
confidence: 99%
“…For graphical models there is a canonical set of "simple" moves, which correspond to the global Markov conditional independence statements. It has been observed that for some models, if a contingency table u has strictly positive margins, then these simple moves connect the fiber of u [6]. Similarly, for the no-three-way interaction model Bunea and Besag proved a positive margins property for a set of "simple" moves [5].…”
Section: Introductionmentioning
confidence: 98%